The effectiveness of pulmonary rehabilitation for Post-COVID symptoms: A rapid review of the literature. (April 2022) - Soril, Lesley J.J.; Damant, Ronald W.; Lam, Grace Y.; Smith, Maeve P.; Weatherald, Jason; Bourbeau, Jean; Hernandez, Paul; Stickland, Michael K.
Abstract: Background: Multi-disciplinary rehabilitation is recommended for individuals with post-acute sequelae of COVID-19 infection (i.e., symptoms 3–4 weeks after acute infection). There are emerging reports of use of pulmonary rehabilitation (PR) in the post-acute stages of COVID-19, however the appropriateness of PR for managing post-COVID symptoms remains unclear. To offer practical guidance with regards to post-COVID PR, a greater understanding of the clinical effectiveness literature is required. Methods: A rapid review of the published literature was completed. An electronic database search of the literature published between July 1, 2020 and June 1, 2021 was performed in MEDLINE, Pubmed, and EMBASE. Primary studies evaluating the clinical effectiveness of PR for individuals with post-COVID symptoms were included. Results: Nine studies evaluating the effectiveness of PR were identified; most were small, experimental or quasi-experimental studies, including 1 RCT, and were primarily of low quality. After attending PR, all studies reported improvements in exercise capacity, pulmonary function, and/or quality of life for individuals with post-COVID symptoms who had been hospitalized for their acute COVID-19 infection. Few studies evaluated changes in post-COVID symptom severity or frequency and, of these, improvements in dyspnea, fatigue, anxiety and depression were observed following PR. Further, no studies evaluated non-hospitalized patients or long-term outcomes beyond 3 months after initiating PR. Conclusions: With limited high-quality evidence, any recommendations or practical guidance for PR programmes for those with post-COVID symptoms should consider factors such as feasibility, current PR capacity, and resource constraints. Highlights: Nine studies evaluating the clinical effectiveness of post-COVID pulmonary rehabilitation were identified. Most studies were small and of low quality. All studies reported improvements in post-COVID patients who had been hospitalized. No studies evaluated non-hospitalized patients or long-term outcomes (>3 months).